Factors that contribute to knowledge sharing behavior among academic staffs: A case study at UiTM Melaka City Campus / Mohd Aliff Md. Sukor and Nur Shafina Md. Saad - Md. Sukor, Mohd Aliff; Md. Saad, Nur Shafina (Faculty of Administrative Science and Policy Studies, 2013)
This research intends to focus more on the knowledge processing aspect with greater emphasis on knowledge sharing which is the key element in the implementation of knowledge management. This research hopes to provide useful insights into how knowledge is being shared in organizations especially in the public organizational like the higher educational institutions. The tacit knowledge that the academic staffs create or gains is embedded in their minds and constitutes the storehouse of an educational institution’s intellectual capital. Therefore, it had been proposed that by sharing their knowledge, it can allow others to enhance their job performance. The objectives of this study were to identify the relationship between the factors (motivation, information technology, communication and organizational culture) and the academic staffs’ knowledge sharing behaviour. The method to conduct this study was through the survey which was distribute in the form of questionnaire to 123 out of 180 population of academic staffs who had become the target group for this study. Several tests were conducted to meet the objectives of the study such as the descriptive analysis, normality analysis, reliability analysis, Pearson’s product-moment correlation and finally the multiple regressions to determine which of the four factors that highly gives significant impact on the academic staffs’ knowledge sharing behaviour. All information and data were collected through the primary and secondary data such as books, internet, journals and etc. This research was hope to contribute something to the educational setting especially UiTM, as the study might provide a review over the organizational conditions in the eyes of the academic staffs.